Medication only improves limb movements while deep brain stimulation improves eye and limb movements during visually-guided reaching in Parkinson’s disease - Munoz, Miranda J.; Arora, Rishabh; Rivera, Yessenia M.; Drane, Quentin H.; Pal, Gian D.; Verhagen Metman, Leo; Sani, Sepehr B.; Rosenow, Joshua M.; Goelz, Lisa C.; Corcos, Daniel M.; David, Fabian J. (Frontiers in Human Neuroscience, 2023)
Background: Antiparkinson medication and subthalamic nucleus deep brain stimulation (STN-DBS), two common treatments of Parkinson's disease (PD), effectively improve skeletomotor movements. However, evidence suggests these treatments may have differential effects on eye and limb movements, although both movement types are controlled through the parallel basal ganglia loops. Objective: Using a task that requires both eye and upper limb movements, we aimed to determine the effects of medication and STN-DBS on eye and upper limb movement performance. Methods: Participants performed a visually-guided reaching task. We collected eye and upper limb movement data from participants with PD who were tested both OFF and ON medication (n = 34) or both OFF and ON bilateral STN-DBS while OFF medication (n = 11). We also collected data from older adult healthy controls (n = 14). Results: We found that medication increased saccade latency, while having no effect on reach reaction time (RT). Medication significantly decreased saccade peak velocity, while increasing reach peak velocity. We also found that bilateral STN-DBS significantly decreased saccade latency while having no effect on reach RT, and increased saccade and reach peak velocity. Finally, we found that there was a positive relationship between saccade latency and reach RT, which was unaffected by either treatment. Conclusions: These findings show that medication worsens saccade performance and benefits reaching performance, while STN-DBS benefits both saccade and reaching performance. We explore what the differential beneficial and detrimental effects on eye and limb movements suggest about the potential physiological changes occurring due to treatment.